2004
DOI: 10.1097/00006676-200401000-00023
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Tumor-Infiltrating Lymphocytes Together with CD4+ Tumor-Infiltrating Lymphocytes and Dendritic Cells Improve the Prognosis of Patients with Pancreatic Adenocarcinoma

Abstract: In pancreatic adenocarcinoma, the presence of CD4+ TILs together with CD8+ TILs serves as a good indicator of the patient's outcome after surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
395
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(420 citation statements)
references
References 17 publications
21
395
3
1
Order By: Relevance
“…In the presence of a relatively high level of CD4 þ T-cell infiltration, patients with a sufficient number of tumour-infiltrating CD8 þ T cells demonstrated a significantly better prognosis. We have previously demonstrated a similar synergistic effect between tumour-infiltrating CD8 þ T cells and CD4 þ T cells in oesophageal squamous cell carcinoma and pancreatic adenocarcinoma Fukunaga et al, 2004). The present study is the first report demonstrating such an effect directly observed in resected human specimens.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the presence of a relatively high level of CD4 þ T-cell infiltration, patients with a sufficient number of tumour-infiltrating CD8 þ T cells demonstrated a significantly better prognosis. We have previously demonstrated a similar synergistic effect between tumour-infiltrating CD8 þ T cells and CD4 þ T cells in oesophageal squamous cell carcinoma and pancreatic adenocarcinoma Fukunaga et al, 2004). The present study is the first report demonstrating such an effect directly observed in resected human specimens.…”
Section: Discussionsupporting
confidence: 81%
“…oesophageal squamous cell carcinoma Nakakubo et al, 2003;Oshikiri et al, 2003;Fukunaga et al, 2004). However, in NSCLC, the role of TILs for the survival of patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Like Zhang et al, 10 we demonstrate (in two separate laboratories using independent testing and analysis) that intraepithelial CD3 þ tumor-infiltrating lymphocytes correlate with disease-specific survival in serous ovarian carcinomas. Likewise, we have confirmed the results of two recent studies 9,11 by demonstrating that intraepithelial CD8 þ tumorinfiltrating lymphocytes correlate with disease-specific survival in the entire study cohort (including all stages and histologies), as well as in the subset of serous ovarian carcinomas.…”
Section: Discussionsupporting
confidence: 55%
“…The prognostic significance of the host immune response, as defined by the presence of tumor-infiltrating lymphocytes, has been studied in ovarian cancer [8][9][10][11] and other cancers [12][13][14][15][16][17][18] Zhang et al 10 identified intratumoral (later named intraepithelial) CD3 þ T-cell infiltration to be an independent prognostic factor in 186 advanced ovarian cancers. Curiel et al 8 demonstrated that infiltration of CD4 þ CD25 þ regulatory T-cells carried a worse prognosis in ovarian cancer.…”
mentioning
confidence: 99%